Program Edu-Eco-School: Optimalisasi Lahan Sekolah untuk Budidaya Tanaman Pangan dan Sayuran Berbasis Instalasi Air Penyiraman - Nurdin, Nurdin; Fakhri, Fakhri; Suprayogi, Imam; Ermiyati; ‘Audah, Safridatul; Gussyafri, Haji; Saily, Randhi; Novan, Andre; Wibisono, Gunawan; Olivia, Monita; Nugroho, Soewignjo Agus; Joehari Jamili, M. (Pelita Masyarakat, 2025)
The Edu-Eco-School Program was implemented as a community service activity at SMPS Khazanah Boarding School, Pujud District, with the aim of optimizing school land through the cultivation of food crops and vegetables supported by a water-efficient irrigation system. This program is significant as it aligns with the Sustainable Development Goals (SDGs), particularly Zero Hunger and Climate Action, which emphasize food security and water resource conservation in education. The implementation stages included land condition surveys, the design and construction of a bore well and PVC pipe network as an irrigation system for plant watering, agricultural training, and mentoring up to the harvesting stage. The program successfully transformed underutilized land into a productive garden with various commodities, such as chili, tomato, corn, and vegetables. The harvest not only met the school’s basic needs but also served as a contextual learning medium for students to practice sustainable agriculture. Overall, this program enhanced school community engagement, improved water-use efficiency, and created a productive green area that supports local food security while strengthening environmental education.